The National Heart Lung and Blood Institute Disparities Elimination through Coordinated Interventions to Prevent and Control Heart and Lung Disease Alliance. (15th May 2022) - Kho, Abel; Daumit, Gail L.; Truesdale, Kimberly P.; Brown, Arleen; Kilbourne, Amy M.; Ladapo, Joseph; Wali, Soma; Cicutto, Lisa; Matthews, Alicia K.; Smith, Justin D.; Davis, Paris D.; Schoenthaler, Antoinette; et al.
Abstract: Objective: To describe the National Heart Lung and Blood Institute (NHLBI) sponsored Disparities Elimination through Coordinated Interventions to Prevent and Control Heart and Lung Disease (DECIPHeR) Alliance to support late‐stage implementation research aimed at reducing disparities in communities with high burdens of cardiovascular and/or pulmonary disease. Study Setting: NHBLI funded seven DECIPHeR studies and a Coordinating Center. Projects target high‐risk diverse populations including racial and ethnic minorities, urban, rural, and low‐income communities, disadvantaged children, and persons with serious mental illness. Two projects address multiple cardiovascular risk factors, three focus on hypertension, one on tobacco use, and one on pediatric asthma. Study Design: The initial phase supports planning activities for sustainable uptake of evidence‐based interventions in targeted communities. The second phase tests late‐stage evidence‐based implementation strategies. Data Collection/Extraction Methods: Not applicable. Principal Findings: We provide an overview of the DECIPHeR Alliance and individual study designs, populations, and settings, implementation strategies, interventions, and outcomes. We describe the Alliance's organizational structure, designed to promote cross‐center partnership and collaboration. Conclusions: The DECIPHeR Alliance represents an ambitious national effort to develop sustainable implementation of interventions to achieve cardiovascular and pulmonary health equity.